Development of Institutional and University-Based Journals in Nigeria: Challenges, Prospects, and Strategies for Sustainable Growth - Niyi Jacob Ogunode; Conrad Ugochukwu UKOZOR; Victor OLUGBENGA AYOKO (Researchparks Publishing, 2026)
Scholarly journals constitute one of the most important mechanisms for disseminating research findings and advancing knowledge within higher education institutions. Universities, as centres of teaching, research, and community service, depend on quality academic journals to communicate scientific discoveries, promote innovation, influence policy formulation, and contribute to national development. In Nigeria, the establishment of institutional and university-based journals has increased considerably due to the expansion of tertiary education and the growing emphasis on research productivity. These journals have provided platforms for publishing indigenous research that addresses national and regional developmental challenges. However, despite their increasing number, many Nigerian journals remain underdeveloped and have not attained the level of quality, visibility, sustainability, and international competitiveness expected of globally recognized scholarly publications. Challenges such as inadequate funding, weak editorial capacity, ineffective peer-review systems, irregular publication schedules, poor digital infrastructure, low international indexing, inadequate compliance with publication ethics, limited policy support, and researchers' preference for foreign journals continue to impede their development. This paper reviews the concept of Nigerian journals, their various types, significance to higher education, major challenges affecting their development, and practical strategies for strengthening institutional and university-based journals. The paper concludes that sustainable funding, editorial capacity building, digital transformation, adherence to international publishing standards, improved government support, stronger research culture, and strategic international collaborations are essential for repositioning Nigerian journals for global relevance and competitiveness.